Increasing the Orthogonality of 4-Pyridiniophenols: An Nmr Study of Their Solvatomagnetism - Caroli-Rezende, M; Martinez-Gomez, F; Rodriguez-Huenchun, V (John Wiley and Sons Ltd, 2025)
The 1H- and 13C-NMR spectra of three substituted N-(4-hydroxyphenyl)pyridinium perchlorates, precursors of solvatochromic 4-pyridiniophenolate betaines, were recorded in deuterated acetone, dimethylsulfoxide, and acetonitrile, and their spectral behavior in these solvents was analyzed as evidence of the solute–solvent interactions present in solution. The effect of the increasing orthogonality between the phenolic and pyridinium fragments was clearly evident from the obtained spectra, thus shedding light on the ground-state structures of their deprotonated solvatochromic derivatives and their interactions with the solvent. © 2025 John Wiley & Sons Ltd.